PENGARUH PENGGUNAAN MEDIA CHATGPT DENGAN METODE TUTOR SEBAYA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 SIANTAR TAHUN AJARAN 2025/2026 - Tambunan, Yesica Febrianti; Sianipar, Herlina Hotmadinar; Siahaan, Tumpal Manahara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using ChatGPT media with the peer tutoring method on the economics learning outcomes of Grade X students at SMA Negeri 1 Siantar in the 2025/2026 academic year. The background of this study was the low learning outcomes in economics, where 68.5% of students had not achieved the Minimum Mastery Criteria (KKM). This research used a quantitative approach with a quasi-experimental design in the form of a Nonequivalent Control Group Design. The population consisted of 337 Grade X students of SMA Negeri 1 Siantar. The samples were selected using cluster sampling technique, namely class X-1 as the experimental class consisting of 35 students and class X-2 as the control class consisting of 32 students. Data collection techniques included tests in the form of pre-test and post-test as well as documentation. The research instrument consisted of 20 multiple-choice questions that had been validated. The results showed that the average post-test score of the experimental class was 8.75, which was higher than the control class score of 5.73. The hypothesis testing using the t-test showed that tcount was 4.12 and ttable was 1.68 at a significance level of α = 0.05. Since tcount > ttable (4.12 > 1.68), Ha was accepted and H0 was rejected. Therefore, the use of ChatGPT media with the peer tutoring method had a significant effect on students’ economics learning outcomes.